Implications of widespread algal biofuels production on macronutrient fertilizer supplies: Nutrient demand and evaluation of potential alternate nutrient sources. (1st April 2015) - Canter, Christina E.; Blowers, Paul; Handler, Robert M.; Shonnard, David R.
Highlights: Evaluated the nutrient demand of large scale biofuel production in the U.S. Compared the nutrients required for two microalgae species. Evaluated sources of nutrients and recycling methods during biofuel production. Wastewater and concentrated animal feeding operations provided the most nutrients. Nutrient recycling methods are key to reducing the impact on fertilizer surpluses. Abstract: Biofuels from microalgae are currently the subject of many research projects to determine their feasibility as a replacement for fossil fuels. In order to be a successful candidate, there must be enough fertilizers available to support large scale production. Commercial fertilizers are available for biofuel production from the world fertilizer surplus, but due to nitrogen and phosphorus future production limitations, biofuels would ideally not use any of these resources to be a long term sustainable fuel. Nitrogen, phosphorus and potassium requirements were determined for two algal species, Chlorella and Nannochloropsis, to produce 19 billion l per year (BLPY). At this scale, both algal species would use 32–49%, 32–49% and less than 1% of the world surplus values of nitrogen, phosphorus and potassium, respectively. Nutrient recycling options and alternative sources of nutrients were evaluated to determine their potential contribution of lowering the synthetic fertilizer requirement. Results show that all of the recycling scenarios reduce the nutrient requirements, but catalytic hydrothermal gasification has the largest reduction of 95% of the nitrogen and 90% of the phosphorus. Contributions from all alternative sources can also provide only 5% or less of the required nitrogen when produced in the gulf region. For phosphorus in the same region, poultry concentrated animal feeding operations can provide up to 28% of the requirement of Chlorella . To find the least amount of nitrogen that may be used, catalytic hydrothermal gasification was combined with all of the alternative nutrients available in the gulf region. The maximum amount of biofuels that could be produced in this location without using any synthetic fertilizers is 50 ± 20 BLPY from Chlorella and 45 ± 19 BLPY from Nannochloropsis . This study shows that the nutrient requirement for biofuel production from microalgae will not be a limitation if recycling methods within the process chain and alternative sources of nutrients are utilized.